John Ruskin an idiosyncratic dictionary encompassing his passions, his delusions & his prophecies - Glover, Michael 1949- (Lund Humphries, 2019)
From Aesthete to Ziffern, Baby-Language to Verbosity, Badgers to Railway Stations: this gloriously serendipitous dictionary presents the life, times and strong opinions of John Ruskin (1819-1900) - art critic, patron, draughtsman, watercolourist, social thinker and philanthropist. Michael Glover's delightful A-Z distills the essence of Ruskin, revealing a lighter side to the man known for his 39 volumes of ponderous prose. When off his guard, Ruskin could write pithily and amusingly, but he was also a fascinating amalgam of self-contradictions. Combining judiciously selected extracts from Ruskin's writings with the author's wittily insightful interpretations, this book is essential reading for all those curious to know what Ruskin did with a cyanometer, why he hated iron railings and the Renaissance, and how Proust's admiration of the man was tinged with distrust
Keywords: Ruskin, John -- 1819-1900; Ruskin, John / 1819-1900 / Criticism and interpretation; Ruskin, John / 1819-1900; Criticism, interpretation, etc; Wörterbuch